2017
DOI: 10.1007/s41547-017-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecium and Enterococcus faecalis in endodontic infections: antibiotic resistance profile and susceptibility to photodynamic therapy

Abstract: Introduction Enterococcus faecium has become an important microorganism in nosocomial infections with great ability to acquire antibiotic resistance. However, little is known about their presence on the oral cavity. Therefore, our objective was to verify the presence of E. faecium and E. faecalis in endodontic infections and compare their susceptibility to conventional antibiotics and photodynamic therapy. Methods We performed 38 collections from the root canals of different patients. Positive Enterococcus aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…The study by Prado et al, 2017 [50] on antibiotic resistance of E. faecium and E. faecalis strains isolated from root canals revealed that E. faecalis was resistant to tetracycline, ciprofloxacin, and azithromycin, while E. faecium was sensitive to all antibiotics tested, suggesting that E. faecium showed higher susceptibility to antibiotics than E. faecalis.…”
Section: Antibiotics Resistance Profilesmentioning
confidence: 99%
“…The study by Prado et al, 2017 [50] on antibiotic resistance of E. faecium and E. faecalis strains isolated from root canals revealed that E. faecalis was resistant to tetracycline, ciprofloxacin, and azithromycin, while E. faecium was sensitive to all antibiotics tested, suggesting that E. faecium showed higher susceptibility to antibiotics than E. faecalis.…”
Section: Antibiotics Resistance Profilesmentioning
confidence: 99%